Gold‐Triggered Uncaging Chemistry in Living Systems. (9th August 2017) - Pérez‐López, Ana M.; Rubio‐Ruiz, Belén; Sebastián, Víctor; Hamilton, Lloyd; Adam, Catherine; Bray, Thomas L.; Irusta, Silvia; Brennan, Paul M.; Lloyd‐Jones, Guy C.; Sieger, Dirk; Santamaría, Jesús; Unciti‐Broceta, Asier
Abstract: Recent advances in bioorthogonal catalysis are increasing the capacity of researchers to manipulate the fate of molecules in complex biological systems. A bioorthogonal uncaging strategy is presented, which is triggered by heterogeneous gold catalysis and facilitates the activation of a structurally diverse range of therapeutics in cancer cell culture. Furthermore, this solid‐supported catalytic system enabled locally controlled release of a fluorescent dye into the brain of a zebrafish for the first time, offering a novel way to modulate the activity of bioorthogonal reagents in the most fragile and complex organs. Abstract : Gold – nicht nur für die Zahnmedizin : Durch heterogene Goldkatalyse können Sonden und therapeutische Wirkstoffe sowohl in vitro als auch in vivo in bioorthogonaler Weise aktiviert werden (siehe Schema; Maßstab 100 μm).